Effects of the Coiling Temperature and Anisotropy on the Tensile Properties of High-Strength API X70 Linepipe Steel - Dong-Kyu Oh; Seung-Hyeok Shin; Sang-Min Lee; Byoungchul Hwang (Archives of Metallurgy and Materials, 2022)
In this study, the effect of the coiling temperature on the tensile properties of API X70 linepipe steel plates is investigated in terms of the microstructure and related anisotropy. Two coiling temperatures are selected to control the microstructure and tensile properties. The API X70 linepipe steels consist mostly of ferritic microstructures such as polygonal ferrite, acicular ferrite, granular bainite, and pearlite irrespective of the coiling temperature. In order to evaluate the anisotropy in the tensile properties, tensile tests in various directions, in this case 0° (rolling direction), 30°, 45° (diagonal direction), 60°, and 90° (transverse direction) are conducted. As the higher coiling temperature, the larger amount of pearlite is formed, resulting in higher strength and better deformability. The steel has higher ductility and lower strength in the rolling direction than in the transverse direction due to the development of γ-fiber, particularly the {111}<112> texture.